Local Literature’s Role In Raising Environmental Awareness: An Ecocritical Study Of Indonesian Texts - Abdurahman Abdurahman; Dedi Gunawan Saputra; Silva Fitri (Yayasan Adra Karima Hubbi, 2025)
Background: Indonesia faces acute environmental crises, including deforestation and marine pollution, which are often disconnected from public discourse. While policy-based solutions are widely discussed, the potential of local literature as a vehicle for shaping ecological consciousness and fostering environmental ethics remains significantly underexplored in academic research. Purpose: This research aims to analyze the specific ecocritical strategies employed in contemporary Indonesian literary texts and to evaluate their effectiveness in raising environmental awareness and critiquing anthropocentric paradigms. Methods: An ecocritical textual analysis was employed as the primary research method. The study analyzed a purposive selection of prominent Indonesian novels and short stories published post-2000 that explicitly engage with themes of ecological degradation, local wisdom (kearifan lokal), and human-nature relationships. Results: The analysis reveals that these texts utilize distinct narrative techniques such as adopting non-human perspectives, invoking indigenous ecological knowledge, and portraying visceral environmental disasters to cultivate empathy. These strategies effectively translate complex ecological data into relatable affective experiences, challenging developmentalist narratives. Conclusion: Contemporary Indonesian literature functions as a vital and potent medium for environmental advocacy. By grounding ecological crises in local cultural contexts, these texts bypass defensive skepticism and successfully foster a critical environmental awareness that policy-making and scientific data alone often fail to achieve.